Faktor Religiusitas dalam Membayar Pajak & Zakat - Abdullah Mujaddid; Greska Redielano Ramadan (Universitas Trunojoyo Madura, 2019)
As we know, tax holds important roles in order to achieve social welfare. However, the shadows of tax evasion which committed either by individually or corporate has been an obstacles to achieve the goals. On the other hand, zakah also takes a big roles in term to achieve social welfare. This research attempts to examine religiosity as variables which influences the willingness to pay tax and zakah. We conducted laboratory experiment to reveal the willingness of the participants. Accounting students posed as experiment participant. Based on the laboratory experiment with online based survey, 70 participants were obtained. The result of this research showed that religiosity has significant impact toward both tax and zakah willingness to pay. Furthermore, the importance of religion, intensity to pray and considering religion values have significant effect toward the willingness of both. The first two religiosity variables have negative impact. However, the consideration of religion values has positive impact. We also found evidence that there is no significant different between willingness to pay tax and zakah in both level of religiousity namely high and low.